Analysis of Sequential Specimens Shows That Breast Implant–Associated Anaplastic Large Cell Lymphoma Behaves as a Lymphoma Rather Than as a Lymphoproliferative Disorder. (21st September 2018) - Evans, Mark; Jeffrey Medeiros, L; Miranda, Roberto
Abstract: Objectives: Breast implant–associated anaplastic large cell lymphoma (BI-ALCL) is a provisional entity accepted in the revised WHO classification. Some authors have suggested that BI-ALCL is similar to CD30-positive lymphoproliferative disorders (LPDs), in that it may regress spontaneously. To better understand the natural history of this disease, we identified patients with BI-ALCL who had previous fine-needle aspiration (FNA) or capsular biopsies before a definitive diagnosis was established. Methods: We searched our institutional database for patients diagnosed with BI-ALCL who had a previous pathologic specimen to compare with their definitive diagnostic material. Results: We identified 11 patients with BI-ALCL who had FNA or capsular biopsies ≥3 months before a definitive diagnosis was established. The previous FNA or capsular biopsies were performed 0.42 to 3 years prior to the definitive diagnostic procedures. The comparison between serial specimens showed persistent disease in seven patients and progression in four patients. Upon diagnosis, the patients had implant removal with complete surgical capsulectomy, and five also received chemotherapy and/or radiation treatments. The median time from diagnosis to last follow-up was 4 years (range, 2–16 years). Ten patients achieved complete remission, and one patient is alive with disease. Conclusion: Follow-up of 11 patients with BI-ALCL with sequential biopsies demonstrates persistence or progression of disease. We did not observe patients who underwent spontaneous regression, consistent with the notion that BI-ALCL is a true lymphoma rather than an LPD.